Leverage, Kepemilikan Publik dan Opini Audit Report Lag - Marlina Putri; Abdallah Rabiu Mohammed Raibu; Ahmad Syukron Ulinnuha (Journal Of Islamic Economics And Finance, 2024)
The purpose of this study was to analyze the factors that influence the delay in audit reports to companies listed on the Indonesia Stock Exchange. The factors studied in this study are leverage, public ownership and audit opinion as independent variables, while audit report lag as the dependent variable. The population in this study is a manufacturing company in the consumer goods sub-sector listed on the Indonesia Stock Exchange. By using purposive sampling motede, obtained as many as 8 companies. The type of data in this study is secondary data in the form of financial statements, and the analysis method uses multiple linear regression analysis and SPSS Version 25 tools. The results of this study indicate that leverage has a significant effect on audit report lag. While public ownership and audit opinion have no effect on audit report lag.